421 Migratory Foreign Bodies in Theaero-Digestive Tract: The Importance of Computerised Tomography (CT) Imaging. (28th February 2022) - Hussain, S.; Muhammad, A.; K K, A.; Khan, M.
Abstract: Aim: We discuss this case to stress the role of computerized tomography imaging in diagnosis of foreign bodies of the upper aerodigestive tract and propose an algorithm for management of such cases. Case Presentation: A 35-year-old male presented with dysphagia and swelling in the left lower part of the neck for 2 days. He gave a history of suspected fish bone ingestion one week prior, followed by pain and discomfort in the throat. Patient underwent upper gastrointestinal endoscopy, which was inconclusive. The patient was reassured and sent home. Examination showed 3 x 4cm soft tender swelling in the left lower part of the neck. Computed tomography showed heterogeneously enhancing soft tissue density with multiple air shadows in the left para-pharyngeal space [fig 1]. Long, narrow, calcified lesion was present in the midst of the soft tissue density, suspected to be a fish bone [fig 2]. Vertical incision was made along the anterior border of the left sternocleidomastoid muscle and 20 ml pus was drained. Carotid sheath was identified and was swollen, surrounded by extensive granulation tissue. Fish bone was found adjacent to the thyroid lobe [Fig 3], was removed - it was serrated and four cm in length [Fig 4]. Repeat endoscopy and a barium meal showed no leak. He was discharged with oral antibiotics for two weeks with no further follow up. Conclusions: Accidental fish bone ingestion is a very common situation in otarhynological emergencies. The role of CT imaging in the management of rare instances like perforation and migration of foreign bodies can prevent serious and life-threatening complications.